2018
DOI: 10.1007/s12031-018-1162-7
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α/Beclin1-Mediated Autophagy Is Involved in Neuroprotection Induced by Hypoxic Preconditioning

Abstract: Hypoxic preconditioning (HPC) exerts a protective effect against hypoxic/ischemic brain injury, and one mechanism explaining this effect may involve the upregulation of hypoxia-inducible factor-1 (HIF-1). Autophagy, an endogenous protective mechanism against hypoxic/ischemic injury, is correlated with the activation of the HIF-1α/Beclin1 signaling pathway. Based on previous studies, we hypothesize that the protective role of HPC may involve autophagy occurring via activation of the HIF-1α/Beclin1 signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 60 publications
3
55
0
2
Order By: Relevance
“…Li et al 34 , reported that FG4592 induced autophagy in SH-SY5Y cells via LC3II/LC3I upregulation and p62 downregulation. The "clinical" PHD inhibitors significantly upregulated Beclin1 in the PC12 cells, which is line with the study by Lu et al 35 showed that HIF-1/ BNIP3/Beclin1 signalling pathway modulates autophagy and contributes to hypoxia preconditioning-induced protection against OGD/Reperfusion. Although rapamycin promoted autophagy (shown by LC3-II upregulation and p62 downregulation), it did not upregulate the expression of Beclin1.…”
Section: Discussionsupporting
confidence: 88%
“…Li et al 34 , reported that FG4592 induced autophagy in SH-SY5Y cells via LC3II/LC3I upregulation and p62 downregulation. The "clinical" PHD inhibitors significantly upregulated Beclin1 in the PC12 cells, which is line with the study by Lu et al 35 showed that HIF-1/ BNIP3/Beclin1 signalling pathway modulates autophagy and contributes to hypoxia preconditioning-induced protection against OGD/Reperfusion. Although rapamycin promoted autophagy (shown by LC3-II upregulation and p62 downregulation), it did not upregulate the expression of Beclin1.…”
Section: Discussionsupporting
confidence: 88%
“…Hypoxic preconditioned-MSCs exert superior protected role and has been confirmed to involve HIF1α and Bec-lin1 signaling pathway in several conditions [96][97][98]. Pretreatment of MSCs with different hypoxic oxygen concentrations have shown promising outcomes in the therapeutics of MCSs by critically influencing their inherent characteristics including reduced senescence.…”
Section: Reducing Premature Senescencementioning
confidence: 99%
“…In recent years, many studies have shown that hypoxia preconditioning (HPC) could increase the resistance of brain to subsequent hypoxic insults [1][2][3]. Gidday et al [4] showed that after pre-exposure to 8% oxygen for 3 h for 1 day, the rat brain can be protected from hypoxic-ischemic injury induced 1 day after HPC.…”
Section: Introductionmentioning
confidence: 99%